Rancangan Virtual Private Server Pada Kantor Kelurahan Menggunakan ZeroTier - Theovan Gracia Stefana Putra; Indrastanti R Widiasari (Forum Kerjasama Pendidikan Tinggi, 2022)
Banyuanyar Village is a guided village developed by the Boyolali Regency Government to become an internet village. The operational activities of the Banyuanyar Urban Village Office also utilize the existing internet network. However, its use is still not optimal and is at risk of being attacked because it uses the same network as general internet users and the Banyuanyar Urban Village Office does not yet have a central server as a database due to limited funds and technicians. Because of this, the activities of the staff who work become sluggish and less effective. Therefore, it takes a Virtual Private Server Design that is useful to support performance. This design uses ZeroTier which can be used as an open-source VPS and VPN and has the latest technology. This research provides effectiveness and security regarding data transfer and network in the Banyuanyar Village Office. Because ZeroTier can be controlled and supervised by admins who can later provide convenience in network management.